Use of the Reversible Myogenic to Lipogenic Transdifferentiation Switch for the Design of Pre-clinical Drug Screening in Idiopathic Pulmonary Fibrosis - Lingampally, Arun; Jones, Matthew R.; Bagari, Shirisha; Chen, Chengshui; Rivetti, Stefano; Bellusci, Saverio (Frontiers in Bioengineering and Biotechnology, 2020)
Idiopathic Pulmonary Fibrosis (IPF) is characterized by excessive extracellular matrix (ECM) deposition from activated myofibroblasts (MYFs) and tissue scarring.. So far two drugs, pirfenidone (acting via TGF-β inhibition) and nintedanib (a pan-tyrosine kinase receptor inhibitor) have been approved for IPF patients. They act on the activated MYF by reducing the expression of fibrotic markers. Unfortunately, these drugs are only slowing down fibrosis formation and do not represent a cure for this lethal disease. We reported that activated MYF partially originate, from lung fibroblast resident cells called lipofibroblasts (LIF). During resolution, these activated MYF can transdifferentiate into LIF. This reversible myogenic/lipogenic transdifferentiation switch paradigm can be used to screen for drugs capable of triggering the lipogenic differentiation of activated MYFs. Ideally, these drugs should also induce the reduction of pro-fibrotic markers (ACTA2 and COLLAGEN 1A1) in activated MYF and as such would represent important alternatives to the approved drugs. The goal of this review is to summarize the current knowledge and limitations of the current strategies aiming to carry out methodical pre-clinical drug screening in pertinent in vitro, ex vivo and in vivo models of IPF. These models include 1) in vitro culture of primary fibroblasts from IPF patients, 2) ex vivo culture of precision cut lung slides from end-stage IPF lungs obtained from transplant patients and 3) bleomycin-induced fibrosis mouse models in the context of lineage tracing of activated MYF during resolution. For all these assays, we propose the innovative use of lipogenic read outs for the LIFs.